Electrospinning of botanicals for skin wound healing - Guo, Shijie; Wang, Pengyu; Song, Ping; Li, Ning (Frontiers in Bioengineering and Biotechnology, 2022)
Being the first barrier between the human body and external environments, our skin is highly vulnerable to injuries. As one of the conventional therapies, botanicals prepared in different topical formulations have been applied as medical care for centuries. With the current increase of clinical requirements, applications of botanicals are heading towards nanotechnologies, typically fused with electrospinning that forms nanofibrous membranes suitable for skin wound healing. In this review, we first introduced the main process of wound healing, and then presented botanicals integrated into electrospun matrices as either loaded drugs, or carriers, or membrane coatings. In addition, by addressing functional features of individual botanicals in the healing of injured skin, we further discussed the bioactivity of botanical electrospun membranes in relevant to the medical issues solved in the process of wound healing. As achieved by pioneer studies, due to infrequent adverse effects and the diversity in resources of natural plants, the development of electrospun products based on botanicals is gaining greater attention. However, investigations in this field have mainly focused on different methodologies used in the preparation of nanofibrous membranes containing botanicals, their translation into clinical practices remains unaddressed. Accordingly, we propose that potential clinical applications of botanical electrospun membranes require not only the further expansion and understanding of botanicals, but also an establishment of standard criteria for the evaluation of wound healing and evolutions of technologies to support the large-scale manufacturing industry.